Initial Features of Hepatic Metastases From Pancreatic Cancer: Histological and Radiolographical Appraisal of Hepatic Micrometastases Detected by Real-Time Fluorescent Imaging. Issue 9 (October 2017) - Katada, Tomohiro; Hashidate, Hideki; Yokoyama, Naoyuki; Sudo, Natsuru; Mitsuma, Koko; Otani, Tetsuya
Abstract : Objective: The pathophysiology of primary-stage hepatic metastases from gastrointestinal cancers may provide clues to their formation. We investigated initial features of hepatic metastases from pancreatic cancer by examining the histologies of radiographically occult hepatic micrometastases. Methods: We examined 133 consecutive pancreatic cancer patients with no evident hepatic metastases on preoperative imaging. An indocyanine green near-infrared camera system was used to detect hepatic metastases during surgery; preoperatively acquired images of patients were then retrospectively reviewed. Results: Hepatic micrometastases were histologically confirmed in 20 patients (15%). Immunohistochemically, the metastatic cells were with higher positivity of carcinoembryonic antigen (100%), p53 overexpression (40%), and Ki-67 labeling index (38%, median). All the micrometastases were portal thromboemboli in the intrahepatic portal triad that invaded extravenous structures, causing desmoplasis, local biliary obstruction, and indocyanine green–contained bile stasis A review of preoperative dynamic computed tomography or magnetic resonance images revealed focal circular alterations presenting as arterioportal shunts in 50% of the patient with micrometastases and 11% of those without ( P < 0.01). Conclusions: Hepatic metastasis from pancreatic cancer involves portal vein thrombosis that alters local circulation and bile stasis at the portal triad; this is detectable by presurgical radiological examination or intraoperative fluorescent imaging.